2007
DOI: 10.1073/pnas.0608447104
|View full text |Cite
|
Sign up to set email alerts
|

β-Sheet core of human prion protein amyloid fibrils as determined by hydrogen/deuterium exchange

Abstract: Propagation of transmissible spongiform encephalopathies is associated with the conversion of normal prion protein, PrP C , into a misfolded, oligomeric form, PrP Sc . Although the high-resolution structure of the PrP C is well characterized, the structural properties of PrP Sc remain elusive. Here we used MS analysis of H/D backbone amide exchange to examine the structure of amyloid fibrils formed by the recombinant human PrP corresponding to residues 90 -231 (PrP90 -231), a misfolded form recently reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
261
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(296 citation statements)
references
References 48 publications
32
261
3
Order By: Relevance
“…Consistent with the established increase in ␤-structure content upon conversion to amyloid (20,29), the only scenario compatible with the present data is that residues within this "core" region stack as single molecule layers with close proximity of same residues in the adjacent PrP molecules. The location of this tightly packed ␤-sheet region correlates remarkably well with recent H/D exchange studies conducted in our laboratory (19), which mapped an exchangeprotected core to residues Ϸ169-221.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Consistent with the established increase in ␤-structure content upon conversion to amyloid (20,29), the only scenario compatible with the present data is that residues within this "core" region stack as single molecule layers with close proximity of same residues in the adjacent PrP molecules. The location of this tightly packed ␤-sheet region correlates remarkably well with recent H/D exchange studies conducted in our laboratory (19), which mapped an exchangeprotected core to residues Ϸ169-221.…”
Section: Resultssupporting
confidence: 65%
“…This critical gap in TSE research largely reflects experimental difficulties in structural studies of large protein aggregates such as amyloid fibrils. Our recent hydrogen/ deuterium (H/D) exchange study has provided an initial lowresolution insight into the location of the ␤-sheet core in the recombinant PrP amyloid (19). However, the molecular architecture of this core region remains unknown.…”
mentioning
confidence: 99%
“…24,25 Instead, a variety of studies have investigated the structure of amyloid fibrils produced in vitro from recombinant PrP. [26][27][28][29][30][31][32][33][34][35] Hereditary prion diseases include C-terminally truncated variants of the PrP, Y145X, Q160X, Y226X, and Q227X. Previously, we showed that the b-sheet content is highly similar in amyloid fibrils of the Y145X and Q160X stop mutants of human PrP.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] There has been some recent progress in defining the molecular architecture of prion amyloid fibers. 13,14 The mammalian prion proteins have a high homology at the sequence and structural level. All mammalian PrP C studied consist of two structurally distinct domains.…”
Section: Introductionmentioning
confidence: 99%